Expression of Transient Receptor Potential Channel Genes and Their Isoforms in Alpha-Cells and Beta-Cells of Human Islets of Langerhans. (3rd August 2022) - Matos, Gabriel M.; Andersson, Björn; Islam, Md. Shahidul
Abstract : Expression of the transient receptor potential (TRP) channel genes and their isoforms in the alpha-cells and the beta-cells of the human islets of Langerhans has not been studied in detail. In this study, we have analyzed the RNA sequencing data obtained from purified human alpha-cells and beta-cells to identify the genes and their isoforms that are expressed differentially in these two cell types. We found that TRPC1, TRPC4, TRPC7, TRPM3, and TRPML1 were differentially expressed in these two cell types. TRPC1, TRPM3, and TRPML1 were expressed at a higher level in the beta-cells than in the alpha-cells. TRPC4 and TRPC7 were expressed at a higher level in the alpha-cells than in the beta-cells. The TRPC4-206 isoform was expressed at a 45-fold higher level in the alpha-cells compared to the beta-cells. Expression of TRPM3-202 was 200-fold and TRPM3-209 was 25-fold higher in the beta-cells than in the alpha-cells. Our study has demonstrated the relative abundance of expression of the TRP channel genes and their isoforms in the human alpha-cells and the beta-cells.